Improved Functional Assays and Risk Assessment for STA1+ Strains of Saccharomyces cerevisiae. (1st April 2021) - Burns, Laura T.; Sislak, Christine D.; Gibbon, Nathan L.; Saylor, Nicole R.; Seymour, Marete R.; Shaner, Lance M.; Gibney, Patrick A.
Abstract: Diastatic yeasts are a major contamination risk to packaged beer. Brewery quality control programs rely on selective microbial growth media and molecular detection of the STA1 gene; however, there is a wide functional range of diastatic activity that remains unresolved by these current methods. Herein, a comprehensive analysis of diastatic yeast selection media using our collection of STA1+ strains is provided. For the preparation of microbial selection media, several factors to control including plate age, autoclave cycling conditions, cupric sulfate, and dipotassium phosphate concentrations are highlighted. Further several functional assays that confirm the variation in diastatic activity across STA1+ strains and show a clear correlation with earlier onset and increasing strength in strains that contain an intact STA1 promoter are presented. Furthermore, a robust and simple plate-based assay to confirm diastatic activity of potential contaminants has been developed. Collectively, these functional assays provide improved risk assessment of re-fermentation in packaged product with the potential for determining contaminant thresholds for different STA1+ strains and weighing in on the decision to destroy beer or issue a product recall.